2015
DOI: 10.1080/2157930x.2015.1049849
|View full text |Cite
|
Sign up to set email alerts
|

Low-carbon development and inclusive innovation systems

Abstract: Low-carbon development (LCD) is a process of structural change of unprecedented magnitude that includes radical changes in technology, institutions, values and policies. It has been proposed that inclusive institutions are crucial for enabling structural change by facilitating different processes of creative destruction. There are reasons to believe that inclusion is also crucial for achieving LCD. We explore why and how social inclusion may support LCD. In so doing, we bridge a gap between research on social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 36 publications
0
13
0
1
Order By: Relevance
“…Therefore, scholars have paid insufficient attention to the ethical acceptability and societal desirability of innovations. With this, we do not want to imply that IS scholars have completely neglected sustainability considerations (e.g., see [24,28,[76][77][78][79][80][81][82][83]). Nevertheless, many of the approaches-particularly the so-called sustainable systems of innovation [79,80] or sustainability-oriented innovation systems [77,82]-remain focused on technological innovation with the aim of environmental protection.…”
Section: Innovation Systems: Merits and Limits In The Light Of Transfmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, scholars have paid insufficient attention to the ethical acceptability and societal desirability of innovations. With this, we do not want to imply that IS scholars have completely neglected sustainability considerations (e.g., see [24,28,[76][77][78][79][80][81][82][83]). Nevertheless, many of the approaches-particularly the so-called sustainable systems of innovation [79,80] or sustainability-oriented innovation systems [77,82]-remain focused on technological innovation with the aim of environmental protection.…”
Section: Innovation Systems: Merits and Limits In The Light Of Transfmentioning
confidence: 99%
“…An IS framework incorporating such institutions has been introduced as inclusive IS, in which "relatively high levels of inclusion characterize the processes of learning and innovation and in which there is a relatively strong focus on innovation addressing the needs of the lower income strata" [81] (p. 284). The inclusive IS framework has been used to analyze a set of empirical cases to show how social inclusion impacts the (wicked) challenges of a low-carbon development.…”
Section: Theoretical and Practical Building Blocks For A New Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…At a high level, policy developers and citizens look to innovation to contribute to the solution of society's "grand challenges" (Kallerud et al, 2013), but there are also specific issues to which innovation is expected to make contributions, such as the introduction of low-carbon technologies (Andersen & Johnson, 2015), agriculture and development (Joseph, 2014), and education. The emphasis on these expectations has increased substantially over the past 15 years (Hicks, 2016;Lindner et al, 2016), and researchers have suggested that it may lead to a new social contract of science and innovation and may fundamentally transform both science and policy making (Kuhlmann & Rip, 2014).…”
Section: Theoretical Precursors To Inclusive Innovationmentioning
confidence: 99%
“…Substantial changes to the way innovation occurs will also require institutional flexibility in the innovation system (Andersen & Johnson, 2015) along the lines of the better governance principles and processes called for by the RRI literature (Owen et al, 2012;von Schomberg, 2012), including "anticipation, participation, deliberation, transparency-to ensure that the process and direction of R&D and innovation better take into account societal preferences and concerns around ethics, sustainability" (Edler & Fagerberg, 2017).…”
Section: How: Governancementioning
confidence: 99%